1949
DOI: 10.1111/j.1365-2672.1949.tb03874.x
|View full text |Cite
|
Sign up to set email alerts
|

The Speed of “Build‐up” of Thermoduric Organisms on Farm Equipment

Abstract: Summary. The history of the thermoduric problem in milk in the Belfast area has been given and an explanation of the cause offered. It has been shown that in Northern Ireland failure to cool the milk does not lead to any marked increase in the number of thermoduric bacteria. Provided there is no definite source of contamination, the build‐up of thermoduric organisms on farm equipment is slow even where production methods are poor and where suitable washing and sterilising of equipment is absent. Even under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1950
1950
1970
1970

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The rate of multiplication probably depends on the environmental conditions as well as on the species and strains involved. Thus, Anderson & Meanwell (1933), Murray (1949) and Thomas, Thomas & Ellison (1953) found that the time taken for an appreciable build up of thermoduric bacteria on farm dairy equipment ranged from 3 to 30 days after really efficient steam sterilization of the equipment, depending on sources and type of contamination, cleansing methods and whether thermoduric streptococci, micrococci or coryneform bacteria became dominant. According to Hammer & Babel (1957) the presence of milk solids on poorly cleansed equipment provides conditions for growth of bacteria which are very similar to those in milk.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of multiplication probably depends on the environmental conditions as well as on the species and strains involved. Thus, Anderson & Meanwell (1933), Murray (1949) and Thomas, Thomas & Ellison (1953) found that the time taken for an appreciable build up of thermoduric bacteria on farm dairy equipment ranged from 3 to 30 days after really efficient steam sterilization of the equipment, depending on sources and type of contamination, cleansing methods and whether thermoduric streptococci, micrococci or coryneform bacteria became dominant. According to Hammer & Babel (1957) the presence of milk solids on poorly cleansed equipment provides conditions for growth of bacteria which are very similar to those in milk.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence the total coliform count was maximum (4.84 x 10 5 cfu/ml) during the rainy months and minimum (2.75 x 10 5 cfu/ml) during the winter months (Table 5). Presence of single coliform bacteria in raw milk and milk products is the indication of faecal and environmental contamination of bacteria 21 . Much higher count of coliform bacteria was found to be common in industrial raw milk than the standards of the other countries and regions of the world.…”
Section: Resultsmentioning
confidence: 99%